2017
DOI: 10.1001/jamaoto.2017.0977
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Treatment of Human Laryngotracheal Stenosis–Derived Fibroblasts

Abstract: IMPORTANCE Laryngotracheal stenosis (LTS) is a fibroproliferative disorder of the glottis, subglottis, and trachea. In models of fibrosis from other organ systems, the CD4+T-cell response has been shown to regulate extracellular matrix deposition. Specifically, helper T cell 2 (TH2) promotes fibrosis, whereas TH1 and associated cytokines have been shown to be antifibrotic. However, this antifibrotic effect of the TH1 response has not been demonstrated in LTS. OBJECTIVE To determine whether the TH1 cytokine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 37 publications
0
31
0
Order By: Relevance
“…Differential methylation patterns can help to elucidate disease mechanisms that occur without (or beyond what is attributable to) genetic mutation, including those underlying cancer, autoimmune, metabolic, and fibrotic diseases; 32,33,56,57 moreover, alterations in methylation pattern can alter the course of monogenic diseases 56 . Whereas other techniques have identified modulation of specific inflammatory and profibrotic pathways in iSGS as well as iatrogenic laryngotracheal stenosis, 2,3,58,59 our data represent the first effort to profile epigenetic regulation in either disease process. We observed hypermethylation—typically associated with transcriptional downregulation—of CpG regions in five genes associated with disparate aspects of cell physiology.…”
Section: Discussionmentioning
confidence: 84%
“…Differential methylation patterns can help to elucidate disease mechanisms that occur without (or beyond what is attributable to) genetic mutation, including those underlying cancer, autoimmune, metabolic, and fibrotic diseases; 32,33,56,57 moreover, alterations in methylation pattern can alter the course of monogenic diseases 56 . Whereas other techniques have identified modulation of specific inflammatory and profibrotic pathways in iSGS as well as iatrogenic laryngotracheal stenosis, 2,3,58,59 our data represent the first effort to profile epigenetic regulation in either disease process. We observed hypermethylation—typically associated with transcriptional downregulation—of CpG regions in five genes associated with disparate aspects of cell physiology.…”
Section: Discussionmentioning
confidence: 84%
“…Aspiration pneumonia secondary to dysphagia 0 (0) Primary fibroblasts were isolated from the biopsy specimens, cultured, and expanded, as previously described. 24 Passage 2 to 4 of the primary fibroblast cell lines were used for the purposes of our experiments.…”
Section: Brush Biopsy Specimen Samplingmentioning
confidence: 99%
“…In iLTS, fibroblasts (FBs) are considered the main effector cell responsible for excessive deposition of extracellular matrix in the trachea lamina propria. iLTS FBs have been demonstrated to be hypermetabolic, displaying increased proliferation, collagen expression, and collagen production compared to non‐iLTS or normal airway FBs 9–11 . Whereas FBs represent the end effector cell in iLTS, the specific pathways promoting this pathologic profibrotic phenotype remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…iLTS FBs have been demonstrated to be hypermetabolic, displaying increased proliferation, collagen expression, and collagen production compared to non-iLTS or normal airway FBs. [9][10][11] Whereas FBs represent the end effector cell in iLTS, the specific pathways promoting this pathologic profibrotic phenotype remain to be elucidated. Recent investigation has demonstrated that the fibrosis observed in iLTS is associated with an aberrant inflammatory response.…”
Section: Introductionmentioning
confidence: 99%